2009
DOI: 10.1002/cbic.200900123
|View full text |Cite
|
Sign up to set email alerts
|

Steric Constraints Dependent on Nucleobase Pair Orientation Vary in Different DNA Polymerase Active Sites

Abstract: Finding the right fit: Herein, we report on the development of novel steric probes and present initial insights into their interplay with DNA polymerases. Our findings provide experimental evidence for varied enzyme-substrate interactions that might account for the varied selectivity previously observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
1
0
1
Order By: Relevance
“…Thus, the same negative interaction with a large C8 atom that leads to the reduced stability of these base pairs may also help reduce the efficiency of incorporation of dCTP opposite the individual nucleotides. These new findings are also in accordance with much previous work that suggests the high fidelity displayed by A family polymerases stems from them having “tight” insertion sites that are sensitive to steric changes. While the standard Watson–Crick (W–C) base pairs, dG:dC, dC:dG, dA:dT, and dT:dA, all have similar shapes and H8­(purine)–H5­(pyrimidine) distances, the overall base pair shape and H8–H5 distance would be significantly increased if dCTP is incorporated opposite CldG, BrdG, OdG, SdG, OdI, or SdI. Thus, if the polymerase insertion site is normally rigid and tightly defined around the cognate W–C base pair shape, detrimental clashing interactions could develop as larger atoms are substituted at the C8 position of dG or OdG.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, the same negative interaction with a large C8 atom that leads to the reduced stability of these base pairs may also help reduce the efficiency of incorporation of dCTP opposite the individual nucleotides. These new findings are also in accordance with much previous work that suggests the high fidelity displayed by A family polymerases stems from them having “tight” insertion sites that are sensitive to steric changes. While the standard Watson–Crick (W–C) base pairs, dG:dC, dC:dG, dA:dT, and dT:dA, all have similar shapes and H8­(purine)–H5­(pyrimidine) distances, the overall base pair shape and H8–H5 distance would be significantly increased if dCTP is incorporated opposite CldG, BrdG, OdG, SdG, OdI, or SdI. Thus, if the polymerase insertion site is normally rigid and tightly defined around the cognate W–C base pair shape, detrimental clashing interactions could develop as larger atoms are substituted at the C8 position of dG or OdG.…”
Section: Discussionsupporting
confidence: 89%
“…Die Veränderung der Einbaueffizienz durch Einführung einer zusätzlichen Methylengruppe in das natürliche Nucleotid ist deutlich größer als der Unterschied zwischen der Methyl‐ und Ethylmodifikation. Ähnliche Effekte wurden bereits in Studien an Enzymen aus derselben Sequenzfamilie beobachtet 4a,f,g…”
Section: Kinetische Daten Der Nucleotideinbauten Durch Klentaq‐wildtyunclassified
“…91 The 5'-triphosphate derivatives of 4'-methyl-and 4'-ethyl-dA and dT have been synthesised and used as steric probes in the active sites of various DNA polymerases, showing that, for example, the more error prone polymerases, such as Dpo4, incorporate the larger triphosphates more readily than selective polymerases, such as Klenow fragment. 92 4'-C-hydroxymethyl-dT has been introduced into gapmer LNA oligonucleotides to assess the effect of RNAse H activity. It was shown that multiple modifications could be made into an LNA oligomer whilst still activating RNAse H recruitment.…”
Section: Oligonucleotide Synthesismentioning
confidence: 99%